Defining Blackness in Colombia - Peter Wade (Journal de la Société des Américanistes)
Defining Blackness in Colombia. This paper looks at the complex relationship between concepts employed by social scientists and those used in everyday practice and discourse, arguing that the standard ideas about how ideas travel from one domain (state, academe, social movements, everyday usage) to another, and become essentialised or destabilised in the process, are often too simple. Changing definitions of blackness in Colombia, through the process of multiculturalist reform and after, are examined with a view to exploring which categories of actors were influential in shaping these definitions and which were involved in essentialisations and de-essentialisations.